Assessment of Thermal Comfort Measurement in Working Environment of Malaysian Manufacturing Industry - Isa, Halim; Mohamad Haidir, Maslan (2007)
Inherently, industrial workers desired optimum thermal comfort in their working environment to perform task comfortably. Besides comfortable working environment, optimum thermal comfort also plays an important role to reduce industrial accidents, thus enhance occupational health in industries. According to Social Security Organization of Malaysia (SOCSO), the numbers of industrial accidents reported caused by environmental factors (including thermal discomfort) from the year 2000 to 2003 were 204 cases, 222 cases, 260 cases and 123 cases respectively [1-4]. Hence, the assessment of thermal comfort in working environment becomes necessary, so that proactive measures can be taken to solve the mentioned issues. The objectives of the research are to assess and analyze current thermal comfort in working environment of manufacturing industry in Malaysia. A case study was carried-out in two manufacturing companies located in Klang Valley. Thermal comfort monitors; BABUC A and QUESTEMP were used to measure thermal quantities of the working environment. Data on each quantity is then interpreted to obtain the mean value of the votes of a large group of worker and percentage of thermally dissatisfied worker, which is expressed in Predicted Mean Vote (PMV) and Predicted Percentage of Dissatisfied (PPD) respectively. Following results were obtained: PMV are 2.45 (minimum), 2.81 (medium) and 3.22 (maximum). Meanwhile PPD are 92.23%, 96.43% and 99.07% for the minimum, medium and maximum, respectively. Based on the results obtained, it can be concluded that the workers experienced thermal discomfort associated with warm working environment and most of them were dissatisfied with the current thermal comfort in their working environment.